Congenital Heart Disease Revealing Familial 22q11 Deletion Syndrome - Santos, Marlene Viviane Pires Fernandes (2021)
Congenital heart defects are the most common birth defects and the leading cause of mortality in the first year of life. It is well known that the 22q11 deletion syndrome (22q11DS) is the most common microdeletion syndrome in humans and that congenial heart diseases (CHDs) are one of the most common phenotypic manifestations. However, it should be noted that the 22q11 deletion was also found in a significant number of patients with isolated CHD. The 22q11DS phenotype may include cardiovascular anomalies, palatal abnormalities, nasal voice, immune deficiency, endocrine dysfunctions, a varying degree of cognitive deficits and intellectual disabilities, velopharyngeal insufficiency, and characteristic craniofacial dysmorphism. This condition affects about 1 in 4,000 live births, making 22q11DS the most common microdeletion syndrome in humans. Here we describe the cases of three children who were referred to the clinical hospital center with the diagnosis of CHD, but with no direct signs of 22q11DS. Investigation of familial data led us to suspect that the mothers could be carriers of 22q11DS. The multiplex ligation-dependent probe amplification (MLPA) testing confirmed that the patients and mothers exhibited 3 Mb 22q11 deletions, which justified the clinical signs in the mothers and the CHD in children. In the presence of a few characteristics that are common of a spectrum of some known syndromes, a familial examination can provide clues to a definitive diagnosis, as well as to the prevention of diseases and genetic counseling of these patients.